Impacts of Water Vapor on Saharan Air Layer Radiative Heating. Issue 24 (23rd December 2019) - Gutleben, Manuel; Groß, Silke; Wirth, Martin; Emde, Claudia; Mayer, Bernhard
Abstract: Airborne lidar observations of long‐range transported Saharan air layers in the western North Atlantic trades indicate increased amounts of water vapor within the dust layers compared to the surrounding dry free atmosphere. This study investigates the impact of such enhanced water vapor concentrations on radiative heating. Therefore, spatially high resolved airborne high spectral resolution and differential absorption lidar measurements are used for the parametrization of aerosol optical properties and water vapor concentrations in radiative transfer calculations. Heating rates that are calculated under consideration of the measured water vapor distribution strongly differ from heating rates that are derived under assumption of an atmospheric reference water vapor profile which is steadily decreasing with altitude. Results highlight that water vapor represents a major radiative driver for dust layer vertical mixing and the maintenance of bounding inversions at the top and bottom of the dust layer. Plain Language Summary: Dust particles are frequently mobilized in the Saharan desert and cross the subtropical North Atlantic Ocean in an elevated atmospheric dust layer, which is termed the Saharan air layer. Airborne remote sensing measurements that were conducted near the Caribbean islands indicate increased water vapor concentrations inside such dust layers compared to the surrounding dust‐free atmosphere. In this work the radiative effect of water vapor in dust layers is investigated for the first time using measurements by an airborne lidar instrument together with a radiative transfer model. It is demonstrated that atmospheric heating due to water vapor is influencing the stability of the atmosphere and is a major driver for the maintenance of thermodynamic structure of the the dust layers. Key Points: Airborne lidar measurements indicate enhanced water vapor concentrations in Saharan air layers compared to the surrounding atmosphere Saharan air layer water vapor strongly modifies atmospheric radiative heating rate profiles Water vapor promotes mixing inside the dust layers and helps to maintain their bounding inversions